Standing Tall: the evolution of habitable room height limits in New Zealand building controls - Isaacs, Nigel (Architectural History Aotearoa, 2021)
Although it is often thought that the 3 February 1931 Napier earthquake led to the first New Zealand building codes, they have a far longer history. Often developed by the local town, city or borough engineer, these codes or by-laws covered a wide range of topics, not just structural safety. Two surveys of local government building bylaws undertaken to support the development of national building controls, have created digests of details from a number of these codes. The 1924 survey of 37 municipalities supported the development of the first national code for timber buildings, while the 1938 survey of 84 municipalities was used to develop NZSS 95 Model Building By-law during the 1930s and early 1940s. The digests provide an opportunity to explore the 1930s development of building by-laws by geographical and topic coverage, as well as the impact on building controls since that time. These local building bylaws often included requirements that affected the interior architecture of buildings, such as the requirement for minimum dwelling or bedroom room heights. In 1924 these minima ranged from 8 ft to 10 ft (2.4 m to 3.0 m) for either a dwelling or an attic room. However, by 1938 while the height range for dwelling rooms was unchanged for attic rooms the range was reduced by 1 foot (0.3 m) to 7 ft to 9 ft (2.1 to 2.9 m). Although the 1992 New Zealand Building Code does not specify minimum habitable room heights, the House Improvement Regulations 1947 are still in force. These initially set the habitable room height requirement to 2.1 m, increasing in 1975 to 2.4 m. The paper explores the development of minimum dwelling height requirements in New Zealand using these two surveys with analysis of Wellington and Dunedin City Councils from the 1870s to the 1930s. These requirements will be compared to UK codes, exploring both the international evolution of room height requirements and the relationship to New Zealand.